2017
DOI: 10.16965/ijar.2017.176
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Study of Anatomical Variations in the Arterial Supply of Vermiform Appendix

Abstract: Acute appendicitis is the most common cause of acute abdomen in young adolescents and appendectomy is often the first major surgical procedure performed by a surgeon. Precise knowledge of vascular variation and planning of conducting surgical and radiological procedures is important during appendectomy. The appendicular artery is considered to be a branch from posterior caecal artery or ileocolic artery entering the mesoappendix from behind the ileum and supplying it. There is no general agreement in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…We noted this source in 12.4% of the total cases, a remarkably higher occurrence compared with the other origins. The prevalence of the specific origin was affirmed by 7 out of 11 studies (excluding Nirmaladevi and Seshayyan, 14 Kalamutharasi 16 and Sudha et al, 17 while Kumari and Srinivas 13 reported an equivalent frequency with the ileal branch). An occurrence of 2% is attributed to the descending branch of the ileocolic artery, which is situated before its division into the cecal arteries.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We noted this source in 12.4% of the total cases, a remarkably higher occurrence compared with the other origins. The prevalence of the specific origin was affirmed by 7 out of 11 studies (excluding Nirmaladevi and Seshayyan, 14 Kalamutharasi 16 and Sudha et al, 17 while Kumari and Srinivas 13 reported an equivalent frequency with the ileal branch). An occurrence of 2% is attributed to the descending branch of the ileocolic artery, which is situated before its division into the cecal arteries.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, our systematic review included 11 studies. [8][9][10][11][12][13][14][15][16][17][18] All studies were performed in Asia and were published between 1930 and 2022. The population of specimens ranged from 20 to 100.…”
Section: Resultsmentioning
confidence: 99%
“…The length of appendix varies from 2 to 20 cm with an average of 9 cm, microscopically the vermiform appendix is a muscular tube containing a large amount of lymphoid tissue. 1 The appendix is suspended by a peritoneal fold called mesoappendix covering its variable length and carrying the blood supply to the organ, by appendicular artery, a branch derived from ileocolic artery. The appendicular artery is an end artery; hence the inflammation of the appendix the vascular thrombosis may produce gangrene of its tip.…”
Section: Introductionmentioning
confidence: 99%
“…The appendicular artery is an end artery; hence the inflammation of the appendix the vascular thrombosis may produce gangrene of its tip. 1 Acute appendicitis is one of the most common causes of abdominal pain in emergency departments. Acute uncomplicated and complicated appendicitis are epidemiologically and clinically different disease entities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation